2003
DOI: 10.1073/pnas.0538042100
|View full text |Cite
|
Sign up to set email alerts
|

Structure and assembly of an augmented Sm-like archaeal protein 14-mer

Abstract: To better understand the roles of Sm proteins in forming the cores of many RNA-processing ribonucleoproteins, we determined the crystal structure of an atypical Sm-like archaeal protein (SmAP3) in which the conserved Sm domain is augmented by a previously uncharacterized, mixed ␣͞␤ C-terminal domain. The structure reveals an unexpected SmAP3 14-mer that is perforated by a cylindrical pore and is bound to 14 cadmium (Cd 2؉ ) ions. Individual heptamers adopt either ''apical'' or ''equatorial'' conformations that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
48
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 37 publications
2
48
0
Order By: Relevance
“…At present we do not know which subunits carry such sites. Structural studies on the SmAP3 (archaeal Lsm protein) homoheptamer and the homooctamer formed by yeast Lsm3 in bacteria reveal that the residues in the C-terminal extension could facilitate intersubunit interactions within the Lsm ring and between two Lsm rings (Mura et al 2003b;Naidoo et al 2008). These observations suggest that the CTD of Lsm1 may also make contacts with the Lsm2 through Lsm7 or Pat1 subunits.…”
Section: Discussionmentioning
confidence: 99%
“…At present we do not know which subunits carry such sites. Structural studies on the SmAP3 (archaeal Lsm protein) homoheptamer and the homooctamer formed by yeast Lsm3 in bacteria reveal that the residues in the C-terminal extension could facilitate intersubunit interactions within the Lsm ring and between two Lsm rings (Mura et al 2003b;Naidoo et al 2008). These observations suggest that the CTD of Lsm1 may also make contacts with the Lsm2 through Lsm7 or Pat1 subunits.…”
Section: Discussionmentioning
confidence: 99%
“…The Lsm1 and Lsm2 proteins have been shown to be associated in vivo (28), so they might also form heteromeric complexes. Crenarchaeota have an additional Lsm protein, Lsm3, which * This work was supported by the Deutsche Forschungsgemeinschaft contains a traditional Sm domain fused to a second domain by a flexible linker (29,30).…”
mentioning
confidence: 99%
“…The Lsm2 protein from Archaeoglobus fulgidus has been reported to form a hexameric (34) or a heptameric (31) complex. The Lsm3 protein has also been shown to form 14-mer complexes (30), a process of which some of the Lsm1 proteins are also capable (35).…”
mentioning
confidence: 99%
“…Members include eukaryotic Lsm (Salgado-Garrido et al, 1999), Sm (Kambach et al, 1999) and SMN/Gemin proteins (Selenko et al, 2001;Ma et al, 2005), archaeal Lsm proteins (Collins et al, 2001), the bacterial protein Hfq (Schumacher et al, 2002) and a recently identified Lsm homolog of cyanophage origin (Das et al, 2009). Eukaryotic genomes can contain up to 16 Lsm and 7 Sm proteins (Albrecht & Lengauer 2004), yet 2-3 Lsm proteins are generally encoded in archaea (Collins et al, 2001;Toro et al, 2002;Mura et al, 2003) and only a single form is evident in bacteria and cyanophage (Schumacher et al, 2002;Das et al, 2009). A characteristic feature of the Lsm proteins is their natural tendency to form ring-shaped quaternary complexes, each of a precise composition related to cellular location and RNA target (Beggs, 2005;Spiller et al, 2007).…”
Section: Phylogeny Of Lsm Protein Sequencesmentioning
confidence: 99%
“…This protein is suggested to be dimeric in solution (Ling et al, 2008). The archaeal protein Pa-Sm3 contains an Lsm-like domain in addition to a C-terminal domain of unknown function adopting an /-fold (Mura et al, 2003).…”
Section: Phylogeny Of Lsm Protein Sequencesmentioning
confidence: 99%